Game Edukasi dalam Pembelajaran Matematika - Muqoddaroh, Fadillatul; Misriah, Zuhaida; Pangura, Asraf Asis; Fakhriyana, Dina (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2024)
The purpose of this study is to provide an overview of the types of educational games used in the mathematics learning process and the influences given from each type of educational game. Systematic Literature Review is a research method in writing this article by taking data about educational games in mathematics learning through the Google Scholar database. The data obtained from the Google Scholar database was then filtered to produce as many as 18 articles relevant to the research objectives. A total of 18 articles were analyzed to produce two points of discussion, namely the type of educational games in mathematics learning and the influence of educational games in mathematics learning. Types of educational games in learning math are Kahoot, Quizizz, and Wordwall. While the influence of educational games in mathematics learning is the understanding of concepts, learning outcomes, learning motivation, confidence, and enthusiasm of students.